Metodología para la construcción de un sistema de flujos de trabajo automatizado (workflow) para empresas de bienes y servicios (2009)
The purpose of this document is to familiarize the reader about the usage of object oriented analysis, design and programming during the development of an automated workflow system for consumer goods and services companies; it provides an insight into the utilized methodology to incite discussions about the future state of workflow systems.